Pengaruh Penggunaan Ecu Standart Dan Ecu Racing Terhadap Daya Dan Torsi Motor Bensin 1 Cilinder - Yovi Veri Asiansah; Mohammad Nur Cholis; Alfiati Hasanah; Agus Setyo Wicaksono; Alexander Herlambang (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2025)
This study aimed to evaluate the differences in power, torque, and fuel consumption of a single-cylinder Honda Vario 125 cc motorcycle by varying the ignition system (standard ECU and racing ECU) and fuel types (Premium and Pertalite). The experimental method involved direct testing using a dynamometer and a burette to collect data, which were then analyzed through graphs and tables. The results showed that the highest power (6.11 kW) and torque (11.63 Nm) were achieved using a racing ECU (curve 2), standard spark plug, and Pertalite fuel, while the lowest power (4.40 kW) and torque (5.22 Nm) were observed with a racing ECU (curve 1), iridium spark plug, and Pertalite. The most efficient fuel consumption (0.044 kg/hour) occurred with a racing ECU (curve 2), standard spark plug, and Pertamax, whereas the highest fuel consumption (0.099 kg/hour) was found with a standard ECU, iridium spark plug, and Pertamax. In conclusion, optimal performance can be achieved by selecting the right ignition system and appropriate fuel with the correct octane rating, specifically using a racing ECU (curve 2), standard spark plug, and Pertalite for power and torque, and Pertamax for fuel efficiency.